Technical and agronomic efficiency of nitrogen use on the yield and quality of oat grains - Mantai,Rubia D. (2021)
ABSTRACT The efficiency of nitrogen use by oats in association with climatic conditions is fundamental to the development of more sustainable managements with yield and quality. The objectives of this study were to define the agronomic efficiency of nitrogen by the ratio of the dose provided and product obtained, estimate the maximum technical efficiency of the nutrient on grain yield; and for the optimum dose, simulate the expression of the straw and industry yields, protein and total fiber in different conditions of the agricultural year in a soybean/oat system. The study was conducted from 2011 to 2016, in Augusto Pestana, RS, Brazil, in a randomized block design with four repetitions in a 4 x 2 factorial referring to nitrogen doses (0, 30, 60 and 120 kg ha-1) and oat cultivars (Barbarasul and Brisasul) in a soybean/oat system. Nitrogen increased grain, straw, and industry yields and total grain protein, with agronomic efficiency of 7.8, 19.7 and 3.3 kg ha-1 and 0.10 g kg-1, respectively, with reduction of the total fiber in 0.05 g kg-1 per kg of N supplied. The dose of maximum technical efficiency in the expression of grain yield is dependent on the weather conditions during cultivation. In general, the maximum efficiency of grain productivity was obtained with 86 kg ha-1 of N, with linear equations showing increased productivity of straw and industry yield, total protein, and reduction of the fiber content of oat grains by nitrogen use.